Biosynthesis of methyl (E)-cinnamate in the liverwort Conocephalum salebrosum and evolution of cinnamic acid methyltransferase. (August 2019) - Zhang, Chi; Chen, Xinlu; Crandall-Stotler, Barbara; Qian, Ping; Köllner, Tobias G.; Guo, Hong; Chen, Feng
Abstract: Methyl ( E )-cinnamate is a specialized metabolite that occurs in a variety of land plants. In flowering plants, it is synthesized by cinnamic acid methyltransferase (CAMT) that belongs to the SABATH family. While rarely reported in bryophytes, methyl ( E )-cinnamate is produced by some liverworts of the Conocephalum conicum complex, including C. salebrosum. In axenically grown thalli of C. salebrosum, methyl ( E )-cinnamate was detected as the dominant compound. To characterize its biosynthesis, six full-length SABATH genes, which were designated CsSABATH1 - 6, were cloned from C. salebrosum . These six genes showed different levels of expression in the thalli of C. salebrosum . Next, CsSABATH1-6 were expressed in Escherichia coli to produce recombinant proteins, which were tested for methyltransferase activity with cinnamic acid and a few related compounds as substrates. Among the six SABATH proteins, CsSABATH6 exhibited the highest level of activity with cinnamic acid. It was renamed CsCAMT. The apparent Km value of CsCAMT using ( E )-cinnamic acid as substrate was determined to be 50.5 μM. In contrast, CsSABATH4 was demonstrated to function as salicylic acid methyltransferase and was renamed CsSAMT. Interestingly, the CsCAMT gene from a sabinene-dominant chemotype of C. salebrosum is identical to that of the methyl ( E )-cinnamate-dominant chemotype. Structure models for CsCAMT, CsSAMT and one flowering plant CAMT (ObCCMT1) in complex with ( E )-cinnamic acid and salicylic acid were built, which provided structural explanations to substrate specificity of these three enzymes. In phylogenetic analysis, CsCAMT and ObCCMT1 were in different clades, implying that methyl ( E )-cinnamate biosynthesis in bryophytes and flowering plants originated through convergent evolution. Graphical abstract: Cinnamic acid methyltransferase (CsCAMT) for making methyl ( E )-cinnamate was identified in the liverwort Conocephalum salebrosum . Structural and phylogenetic analysis suggests that CsCAMT and its counterpart in flowering plants evolved independently. Image 1 Highlights: Methyl cinnamate in the liverwort Conocephalum salebrosum is biosynthesized by cinnamic acid methyltransferase (CsCAMT). CsCAMT is a member of the SABATH family of methyltransferases. Cinnamic acid methyltransferase in liverworts and flowering plants evolved independently.